The Influence of Dormitory Environment and Character Development on Student Learning Motivation at Bumi Kartika Asri Jatinangor - Aris Sukmawan Permana; Deden Komar Priatna; Winna Roswinna (Greenation Research & Yayasan Global Resarch National, 2024)
The dormitory environment from the field questionnaire results is very conducive, starting from all the facilities and infrastructure in the student learning process, this is in accordance with the results of the responses from the respondents. Character development is a management program. From the field results data, all respondents gave very positive responses and the respondents, namely students, were very appreciative of all development programs that could help students develop their religious and social potential. Student learning motivation at the Bumi Kartika Asri dormitory in Jatinangor is an encouragement for students to always be tenacious in completing their assignments, be persistent, be able to show their interests and talents, and always pay attention to their enthusiasm and desire to succeed. The influence of the dormitory environment and the character development program on student learning motivation at Bumi Kartika Asri Jatinnagor from the results of field data stated that there was a significant influence because it could be proven by the results of data analysis using the SPSS for Windows program.